2021
DOI: 10.1016/j.ijscr.2021.106463
|View full text |Cite
|
Sign up to set email alerts
|

Management of incidentally detected idiopathic pneumoperitoneum: A case report and literature review

Abstract: Introduction Pneumoperitoneum usually requires emergency surgery. Asymptomatic idiopathic pneumoperitoneum is a rare subgroup of pneumoperitoneum for which a management algorithm has not been established. Presentation of case In an 88-year-old female patient, pneumoperitoneum was found incidentally by chest computed tomography during a periodic follow-up for sarcoidosis. Emergency admission was ordered for conservative treatment. Upper gastrointestinal endoscopy reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This diverse symptomatology renders the preposition for a standard treatment protocol for pneumoperitoneum based on clinical presentation hard to conceive. Sakaguchi et al proposed an algorithm in 2021 [12] for the initial management of pneumoperitoneum, considering specific symptoms such as peritonitis, ascites, and sepsis. The algorithm entails an escalation of management options ranging from 'careful follow-up' to the 'operating room.'…”
Section: Discussionmentioning
confidence: 99%
“…This diverse symptomatology renders the preposition for a standard treatment protocol for pneumoperitoneum based on clinical presentation hard to conceive. Sakaguchi et al proposed an algorithm in 2021 [12] for the initial management of pneumoperitoneum, considering specific symptoms such as peritonitis, ascites, and sepsis. The algorithm entails an escalation of management options ranging from 'careful follow-up' to the 'operating room.'…”
Section: Discussionmentioning
confidence: 99%
“…IP is quite rare and to the best of our knowledge not adequately reported in the literature. In cases where pneumoperitoneum is nonsurgical or idiopathic, there has been unnecessary explorative laparotomies, typically causing more harm than benefits [ 1 , 5 ]. The current literature suggests if a patient does not have any peritoneal symptoms and if imaging examinations show absence of abdominal cavity pathology, then, clinicians may consider spontaneous pneumoperitoneum, which does not require surgical intervention [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and clinical manifestations vary per individuals, and in about 90% of cases associated with visceral perforation are linked with gastric and duodenal ulcer. The other 10% of cases, broadly described as idiopathic pneumoperitoneum (IP) have no direct connection with a demonstrable risk factor [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experience shows that diagnostic laparoscopy can be beneficial to such patients especially facing generalized peritonitis. It has been shown that patients admitted with moderate symptoms and no signs of infection can be primarily observed and have a better course if a conservative line of treatment is followed [ 8 , 9 ]. In patients with risk factors for perforation of hollow organs, it is important to exclude such a complication, which can also be done by endoscopy if the patient’s condition permits [ 5 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%